Konten Radikalisme berbasis Agama pada Siaran Televisi - Fatwa, Ah. Fajruddin (Jurnal Komunikasi Islam, 2023)
This article discusses the role of broadcast media in spreading religious-based radicalism content in Indonesia. Using a literature review, this study found three negative impacts of broadcasting institutions, especially television, on Indonesian society. First, spreading hateful information against certain social or religious groups. Second, the potential for national disintegration due to the spread of media content that is contrary to national values. Third, the emergence of potential legal violations that occur due to weaknesses in monitoring digital-based broadcast content. From here, it is necessary to increase the capacity of the Indonesian Broadcasting Commission (KPI), restore contradictory statement regulations and norms in broadcasting behavior guidelines and broadcasting behavior standards, as well as the need for institutional coordination between state institutions.